PERAN TIM PAAREDI (POLA ASUH ANAK DAN REMAJA DI ERA DIGITAL) DALAM PERSPEKTIF HUKUM ISLAM - Hariyadi, Riski; Hasim, Fuad; Yuliawati, Tita; Putri, Nerisma Eka (al-Rasῑkh: Jurnal Hukum Islam, 2024)
Family Welfare Empowerment (PKK) is a community organization that empowers women to participate in Indonesia's development. PKK has been regulated in Presidential Regulation No. 99/2017 on the Family Empowerment and Welfare Movement.  One of the PKK priority programs is parenting children and adolescents. PPK Rambah village, Tanah Tumbuh sub-district, Bungo district has a flagship program, namely Parenting Children and Youth in the Digital Age (PAAREDI). In Rambah village, there is a PAAREDI structure consisting of the chairman, secretary, treasurer, membership field, socialization and communication field, education field, and talent and character field. The membership field is responsible for bookkeeping data on children aged 0-6 years, 7-12 years and 13-18 years.  The socialization field is in charge of arranging counseling schedules, finding resource persons, and sharing activities and materials on social media. The education sector is tasked with providing material on religion, pkbn, kdrt, pornography, hiv and the dangers of drugs. Then the field of talent and character is in charge of assisting children's interests and talents, as well as the formation of children's character in the family, fellow friends and society.  In Islam, the role of the PAAREDI team in Rambah Village is in line with the objectives of maqashid shari'ah, namely hifz din, hifz nafs, hifz 'aql, hifz nasl, and hifz mal.